1973
DOI: 10.1021/ja00800a044
|View full text |Cite
|
Sign up to set email alerts
|

Photoalkylation of peptides. Visible light-induced conversion of glycine residues into branched .alpha.-amino acids

Abstract: Amino-3-cyano-5-methyl-6-methoxypyrazine 4-Oxide (11). A solution of 0.50 g of 2-amino-3-cyano-5-methylpyrazine 1,4-dioxide in 20 ml of dry methanol containing 0.43 g of sodium methoxide was heated under reflux overnight. The resulting brownish-red solution was evaporated to about half its volume under reduced pressure, cooled, and filtered. The collected solid was crystallized from acetic acid (charcoal) to give 0.25 g (46%) of colorless crystals: mp >235°dec; nmr (CF3COOH) 2.07 (3, s, C5-CH3), 3.71 (3, s, OC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0
2

Year Published

1998
1998
2012
2012

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 0 publications
2
33
0
2
Order By: Relevance
“…α-carbon hydrogen abstraction accounts for more than 90% of the radicals formed from series of alanine-derived peptides upon reaction with hydroxyalkyl radicals. α-carbon radicals have greater stability over the primary alkyl radicals formed by hydrogen atom abstraction of methyl side chains [33]. The same statement is true for the glycine residues which are found in collagen.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…α-carbon hydrogen abstraction accounts for more than 90% of the radicals formed from series of alanine-derived peptides upon reaction with hydroxyalkyl radicals. α-carbon radicals have greater stability over the primary alkyl radicals formed by hydrogen atom abstraction of methyl side chains [33]. The same statement is true for the glycine residues which are found in collagen.…”
Section: Resultsmentioning
confidence: 98%
“…Since collagen is rich in glycine, this amino acid is favorable for the formation of a secondary α-carbon radical which is more stable than the tertiary radicals formed from other amino acids [32]. However, theoretical calculations have shown that the stability of α-carbon radicals varies with secondary structure as a result of the constraints that such structure plays on the geometry of the α-carbon radical [33]. These species are therefore less stable, and attack at the α-carbon would be expected to be less favorable, when present in a sheet or helix conformation.…”
Section: Resultsmentioning
confidence: 99%
“…This oxidation implies previous hydrogen abstraction with the formation of an α carbon radical and further linking to O 2 (Fu et al, 1995). Not all α carbon radicals showed similar stability, but radical formation in Gly residues in peptides was already observed (Schwarzberg et al, 1973). This justifies the attribution to a peroxy group in Gly residue [ Fig.…”
Section: + the Fragmentation Of The [M + H]mentioning
confidence: 86%
“…An attempt to selectively brominate Nbenzoylvaline methyl ester in the presence of the corresponding glycine derivative resulted in preferential reaction of the glycine derivative. 17,18 A similar selectivity for reaction of glycine derivatives had been observed previously in biochemical systems 19 and through EPR studies of reactions of peptides and proteins, 20 and it had been exploited by Elad et al, [21][22][23][24][25] in the selective free radical alkylation of glycine residues in peptides and proteins. Reactions of this type occur without racemisation of other amino acid residues, which can therefore act as chiral auxiliaries in the production of the new chiral centre at the αcarbon of the glycine residue (Scheme 1).…”
Section: Regioselective Free Radical Functionalisation Of Amino Acid mentioning
confidence: 59%
“…Reactions of this type occur without racemisation of other amino acid residues, which can therefore act as chiral auxiliaries in the production of the new chiral centre at the αcarbon of the glycine residue (Scheme 1). [24][25][26][27] Scheme 1…”
Section: Regioselective Free Radical Functionalisation Of Amino Acid mentioning
confidence: 99%